S01-4: The Evaluation of a Nationwide Implementation of the “Living Well With COPD” Self-Management Programme in Switzerland in Persons With COPD (Baltic Journal of Sport and Health Sciences, 2026)
Introduction: Following its initial pilot implementation in 2017, the “Living well with COPD” self-management programme has been scaled nationwide by the Swiss Lung Associations since 2019. The aim of this mixed-methods study was to evaluate the real-world effectiveness and the experience of new coaches with the programme until February 2025.Method: The programme incorporates six weekly group modules provided by a coach, followed by four phone-calls. It aims to support patients in managing their disease and adopting healthy lifestyle behaviours, including increasing physical activity. To evaluate the effectiveness, we assessed disease specific quality of life (Chronic Respiratory Questionnaire, CRQ), exercise capacity (1-min sit-to-stand test, 1-min STS), symptoms (COPD Assessment Test, CAT), number of exacerbations (